Orange and mango byproducts: agro-industrial waste as source of bioactive compounds and botanical versus commercial description: a review - Delgado, Clarissa Hamaio Okino [UNESP]; Fleuri, Luciana Francisco [UNESP] (Taylor & Francis, 2015)
Vegetal origin agro-industrial wastes are seen as a problem since the beginning of the industrial processes; however, they are becoming attractive as raw material for numerous purposes such as active enzymes and in the molecule bioprospecting area. Moreover, it is difficult to understand what the studied residue is consisted of in studies on agro-industrial waste, since the wastes names and constituents may vary according to the used equipment, as for waste from orange and mango processing. Thus, defining a specific waste, including comparisons between botanical and industrial descriptions, can help in understanding studies about wastes. The current review sought to contextualize such a scenario by gathering definitions, relevant information and studies on agro-industrial wastes and by-products, international enzymes market, and recent studies on bioactive compounds. In this context, waste from orange and mango are interesting because of the expression of these fruits on the world market; moreover, the processing does not include steps that could disrupt these biomolecules.